Inotropic changes in the left ventricle: the effect of changes in heart rate, aortic pressure and end-diastolic pressure - Furnival, C. M. (1970)
1. Under conditions where heart rate, mean aortic pressure and enddiastolic pressure in the left ventricle are held constant, the intravenous infusion of isoprenaline is accompanied by large changes in dP/dt max in the left ventricle. 2. Under similar conditions, during stepwise increments in the rate of infusion of isoprenaline the changes in dP/dt max (measured at a constant paced heart rate) were proportional to changes in the free (intrinsic) heart rate. It is concluded that dP/dt max is a quantitative index of inotropic changes in the left ventricle. 3. In comparison to dP/dt max, three other variables which have been used to indicate inotropic changes in the heart (peak pressure in the left ventricle, duration of systole and stroke work at constant end-diastolic pressure), were shown to be unreliable indices of inotropic changes. 4. Using dP/dt max to indicate inotropic changes, alteration in the heart rate while mean aortic pressure and end-diastolic pressure in the left ventricle were held constant, and in mean aortic pressure while heart rate ane end-diastolic pressure in the left ventricle were held constant, were each shown to be accompanied by small inotropic changes in the heart. 5. Under similar conditions, changes in end-diastolic pressure in the left ventricle alone were not accompanied by inotropic changes as indicated by dP/dt max.